The transparent body : a cultural analysis of medical imaging - Dijck, José van (In vivo (Seattle, Wash.), 2005)
Annotation "Drawing on examples that are international in scope, The Transparent Body examines the dissemination of medical images to a popular audience, advancing the argument that medical imaging technologies are the material embodiment of collective desires and fantasies - the most pervasive of which is the ideal of transparency itself. The Transparent Body traces the cultural context and wider social impact of such medical imaging practices as X-ray and endoscropy, ultrasound imaging of fetuses, the filming and broadcasting of surgical operations, the creation of plastinated corpses for display as art objects, and the use of digitized cadavers in anatomical study."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.